2023
DOI: 10.3390/ijms241311175
|View full text |Cite
|
Sign up to set email alerts
|

Dispersant and Protective Roles of Amphiphilic Poly(ethylene phosphate) Block Copolymers in Polyester/Bone Mineral Composites

Abstract: Composites of synthetic bone mineral substitutes (BMS) and biodegradable polyesters are of particular interest for bone surgery and orthopedics. Manufacturing of composite scaffolds commonly uses mixing of the BMS with polymer melts. Melt processing requires a high homogeneity of the mixing, and is complicated by BMS-promoted thermal degradation of polymers. In our work, poly(L-lactide) (PLLA) and poly(ε-caprolactone) (PCL) composites reinforced by commercial β-tricalcium phosphate (βTCP) or synthesized carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 108 publications
(198 reference statements)
3
4
0
Order By: Relevance
“…42 Subsequent studies demonstrated that even minimal changes in the reaction conditions and component ratios precluded obtaining crystallites of reproducible size and morphology; a method with reliable reproducibility could only be developed for two types of CAp, namely, (a) hexagonal prismatic CAp with an aspect ratio of 0.8−1 and width of 4−8 μm (hCAp) and (b) aggregates of platelike crystallites (pCAp). 43 It is noteworthy that the size and shape of hCAp and pCAp samples prepared and characterized in the present work (Figure 1a,b, see also Figures S1 and S2 in the SI) were close to those of their counterparts synthesized previously (Figure S5 in the SI). 43 XRD studies of the samples confirmed B-type CAp identity, and TGA and FT-IR data showed that incorporation of CO 3 2− anions was higher for hCAp as compared to pCAp (for details, see Section S1 in the SI).…”
Section: Repeatability and Statistical Analysissupporting
confidence: 83%
See 4 more Smart Citations
“…42 Subsequent studies demonstrated that even minimal changes in the reaction conditions and component ratios precluded obtaining crystallites of reproducible size and morphology; a method with reliable reproducibility could only be developed for two types of CAp, namely, (a) hexagonal prismatic CAp with an aspect ratio of 0.8−1 and width of 4−8 μm (hCAp) and (b) aggregates of platelike crystallites (pCAp). 43 It is noteworthy that the size and shape of hCAp and pCAp samples prepared and characterized in the present work (Figure 1a,b, see also Figures S1 and S2 in the SI) were close to those of their counterparts synthesized previously (Figure S5 in the SI). 43 XRD studies of the samples confirmed B-type CAp identity, and TGA and FT-IR data showed that incorporation of CO 3 2− anions was higher for hCAp as compared to pCAp (for details, see Section S1 in the SI).…”
Section: Repeatability and Statistical Analysissupporting
confidence: 83%
“…43 It is noteworthy that the size and shape of hCAp and pCAp samples prepared and characterized in the present work (Figure 1a,b, see also Figures S1 and S2 in the SI) were close to those of their counterparts synthesized previously (Figure S5 in the SI). 43 XRD studies of the samples confirmed B-type CAp identity, and TGA and FT-IR data showed that incorporation of CO 3 2− anions was higher for hCAp as compared to pCAp (for details, see Section S1 in the SI).…”
Section: Repeatability and Statistical Analysissupporting
confidence: 83%
See 3 more Smart Citations